(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides scientific information on the role of preventive measures in animal health, their types, current problems and ways to overcome them. The effectiveness of existing preventive methods, in particular immunization, zoohygienic measures and monitoring systems has been analyzed. Recommendations are also made based on best practices applied in Uzbekistan and other countries.